DOES PARENTING STYLE AFFECT ADOLESCENT EMPATHY? A STUDY ON HIGH SCHOOL STUDENTS - Ramadhanti, Auliya; Putra, Rahman Pranovri; Rizky, Deo Alfa (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
The research is the result of applied science in education, which aims to determine whether there is a relationship between the type of parenting style and the empathetic attitude of students at High school 2 Solok City. This research uses quantitative correlational methods. Data was collected using a parenting style scale with 31 items and an empathy scale with 17 items. The population in this study was 317 students of Senior high school 2 Solok City, and the sample was 176 students. A simple random sampling technique determines the sample. Then, the data was analyzed using Pearson Product Moment correlation analysis. The results of this study show that the level of empathy is in the medium category. The types of parenting patterns for Senior high school 2 Solok City students are divided into 3, namely authoritarian parenting, democratic parenting, and permissive parenting. Of the three types of parenting patterns, the most influential and dominant parenting style used by parents of Solok City 2 High School students is democratic parenting. The correlation test results between the type of parenting style and empathy show that authoritarian parenting and empathy do not have a significant relationship with a personal correlation coefficient value of -0.091; Democratic parenting and empathy have a positive and significant relationship with the person correlation coefficient value. It is significant with a person's correlation coefficient of 0.640, and permissive and empathetic parenting styles have a negative relationship with a person's correlation coefficient of -0.21. The Pearson correlation coefficient is -0.218.